(Em) Serra de Maracaju, Sonhos Guaranis - Faccioni, Flávio (2020)
With the general objective of problematizing the representations of the original peoples in the songs of Almir Sater, Geraldo Espíndola and Paulo Simões, and with the specific objectives of apprehending the meaning effects of the discourses; analyzing representations of land, identity, history and memory from the discursive constructions contained in corpora, and to expand and intensify the discussions about the representations of the original peoples in the speeches, this work brings an interpretative gesture of the songs, Kikio (Geraldo Espíndola), Sonhos Guaranis (Almir Sater and Paulo Simões) and Serra de Maracaju (Almir Sater and Paulo Simões) . I start from the hypothesis that the original peoples are represented by a colonial imaginary, fed by an archive which is still colonial. The question that guides the analytical/interpretative gesture in this text is: how are the original peoples represented in the analyzed songs? As a theoretical support, I rely on French school Discourse Analysis, but I also share history, music, culturalist, geographical and mythological studies, which enable me to develop a heterogeneous and plural work. I use the methodological procedures of Foucault's archaeology to destabilize the statements and to develop field research and interviews. I organize this text in three chapters; in the first one I build the conditions of production of the work and present the songs and the authors. In the second chapter, I undertake the theoretical concepts that I use in the text, presenting and expanding them. Chapter three is dedicated to analyses, reflections from the utterances of the songs and their crossover at the end of the chapter. Through the analyses, I observe that the songs exhort the formation of the people of Mato Grosso do Sul, the history of the original peoples in confrontation with the surrounding society and the memory that is still constituted by an imaginary full of traces of colonialism and of a colonial archive.